METHODS AND WAYS OF TEACHING PRONUNCIATION - Mamatkarimov Sunnat Umidjon o’g’li ("Conference on Universal Science Research 2023", 2023)
This article discusses pronunciation and its types. In addition, the article also talks about different methods of teaching pronunciation.